Images, texts, and marginalia in a "Vows of the peacock" manuscript (New York, Pierpont Morgan Library MS G24) : with a complete concordance and catalogue of peacock manuscripts - Leo, Domenic (Library of the written word, 2013)
The ""Vows of the Peacock"" was composed in 1312 in France. One of the extant manuscripts stands out for its beautiful miniatures and scurrilous marginalia (PML, MS G24). It includes a catalogue and concordance of all Peacock manuscripts.